Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Producing the patchwork: The hidden work of mothers in organizing child care. - Breitkreuz, Rhonda; Colen, Kerryn; Horne, Rebecca (Journal of Family Studies, 2021)
This article aims to explore how child care is organized in families, documenting how mothers produce their individual child care solution, or “patchwork”, within the context of Canada’s underfunded and fragmented child care system. In a sample of 109 mothers from Alberta, Canada, where child care is conceptualized as primarily a private family responsibility, we use an ecocultural theoretical framework and a gender lens to 1) identify the constraints that influenced what kinds of child care mothers used, 2) explore the organization of day-to-day child care arrangements, and 3) explicate the accommodations and flexibility required to sustain the family routine. We show that in addition to previously recognized categories of child care—formal, informal, and mixed—families also used multiple informal and parent-plus (i.e., parental plus non-parental) child care. The procurement and management of child care—particularly when multiple care providers were involved—was gendered, often invisible, and required substantial accommodations and flexibility by mothers. We propose a day-care plus policy model of child care, where formal arrangements are supplemented as required. This policy model could help families avoid the complex scenarios we conceptualize as chaotic flexibility and assist families in achieving sustainable flexibility in the organization of care. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; canada; charge mentale; charge mentale des femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; soins aux enfants; stratégie alternative de garde d'enfants; système de garderie; thématiques; travail; travail de reproduction